1992
DOI: 10.1002/bjs.1800790613
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative infection and natural killer cell function following blood transfusion in patients undergoing elective colorectal surgery

Abstract: The frequency of infection in 197 patients undergoing elective colorectal surgery and having either no blood transfusion, transfusion with whole blood, or filtered blood free from leucocytes and platelets was investigated in a prospective randomized trial. Natural killer cell function was measured before operation and 3, 7 and 30 days after surgery in 60 consecutive patients. Of the patients 104 required blood transfusion; 48 received filtered blood and 56 underwent whole blood transfusion. Postoperative infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
369
1
11

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 540 publications
(398 citation statements)
references
References 17 publications
17
369
1
11
Order By: Relevance
“…The association between blood transfusion and infectious complications in the perioperative period has been well described previously [2,3,27]. This association appears to be consistent amongst cohorts that received either whole blood or leukodepleted blood.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…The association between blood transfusion and infectious complications in the perioperative period has been well described previously [2,3,27]. This association appears to be consistent amongst cohorts that received either whole blood or leukodepleted blood.…”
supporting
confidence: 74%
“…The unintended clinical consequences of immune modulation by allogenic blood in the perioperative period include an increased susceptibility to infectious complications and cancer recurrence [2,3]. As inpatient non-cardiac surgery has recently been associated with much higher than anticipated mortality rates, it is now imperative that all potentially avoidable causes of excess morbidity in this population are investigated and addressed [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two of the three studies that showed differences, the observed effects were much larger than seems biologically plausible. 12,13 One trial found a reduction in mortality associated with leukoreduction, although infection rate was not significantly improved. 14 Thus, a meta-analysis is needed.…”
mentioning
confidence: 99%
“…We conclude that potato starch derived hydroxyethyl starch compromises in vitro blood coagulation more than corn starch derived hydroxyethyl starch. Avoiding allogeneic blood transfusion has become an important issue in surgery and intensive care medicine with increasing awareness of the potential side-effects [1,2]. Besides transmission of infectious diseases, the increased incidence of postoperative infections with prolonged hospitalisation and increased costs [3] has recently created much interest.…”
mentioning
confidence: 99%